2018
DOI: 10.1245/s10434-018-6413-x
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced Spectral Mammography is Comparable to MRI in the Assessment of Residual Breast Cancer Following Neoadjuvant Systemic Therapy

Abstract: CESM was comparable to MRI in assessing residual malignancy after completion of NST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
56
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 22 publications
14
56
1
Order By: Relevance
“…Difference between CEM and histopathological results was within 1 cm in almost 70% of the cases. A similar difference was reported in a recent study with patients submitted to neoadjuvant chemotherapy and endocrine therapy [ 20 ]. Limit of agreement with the residual tumor was narrower for CEM and wider for MRI, the opposite of what was found by Patel and colleagues [ 20 ].…”
Section: Discussionsupporting
confidence: 87%
“…Difference between CEM and histopathological results was within 1 cm in almost 70% of the cases. A similar difference was reported in a recent study with patients submitted to neoadjuvant chemotherapy and endocrine therapy [ 20 ]. Limit of agreement with the residual tumor was narrower for CEM and wider for MRI, the opposite of what was found by Patel and colleagues [ 20 ].…”
Section: Discussionsupporting
confidence: 87%
“…They reported good correlation between both modalities (agreement: 0.76) and thus they concluded that CESM is as reliable as MRI and may be used as an adequate alternative [2]. In another study, Patel et al concluded that the accuracy of CESM was equivalent to MRI in assessing residual disease after NAC [13]. However, these two studies depend on residual tumor size assessment.…”
Section: Discussionmentioning
confidence: 98%
“…To our knowledge, this work is the first research that uses objective and quantitative mathematical evaluation using CESM. Previous published articles in literature in the same setting have only used subjective qualitative assessment methods and quantitative assessments only relied on measuring change in tumor size based on RECIST and measuring size of residual disease which is liable to over or under estimation [2,13]. None of these researches discussed quantitative change in intensity of contrast uptake which reflects actual change in tumor cell activity.…”
Section: Introductionmentioning
confidence: 99%
“…Contrast (iohexol)‐enhanced spectral mammography (CESM) was compared to MRI by Patel et al in the assessment of tumor response for 65 patients after NAC. There were 34 rCRs for CESM and 33 for MRI.…”
Section: Discussionmentioning
confidence: 99%